2004
DOI: 10.1111/j.1368-5031.2004.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age, seropositivity and disease duration on autonomic cardiovascular reflexes in patients with rheumatoid arthritis

Abstract: Previous studies have shown that autonomic cardiovascular reflexes (ACRs) are impaired in rheumatoid arthritis (RA) and in old age. To investigate the integrity of ACRs in patients with RA, with reference to age, duration of disease and rheumatoid factor (RF) positivity, we conducted a prospective open study of 62 RA outpatients (age 38-84) and 41 healthy controls (age 22-82) using five standard tests of ACR function. Patients of all ages with RA were found to have blunted ACRs when compared with younger contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
16
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 23 publications
(31 reference statements)
4
16
1
Order By: Relevance
“…Significantly higher resting pulse rate and diastolic blood pressure in the RA patients may be attributed to the lower parasympathetic higher sympathetic activity which is consistent with the observation made by Sandhu and Allen 19 .…”
Section: Discussionsupporting
confidence: 81%
“…Significantly higher resting pulse rate and diastolic blood pressure in the RA patients may be attributed to the lower parasympathetic higher sympathetic activity which is consistent with the observation made by Sandhu and Allen 19 .…”
Section: Discussionsupporting
confidence: 81%
“…Several investigators assessed cardiovascular autonomic nerve function in RA patients and observed cardiovascular autonomic nervous system dysfunction [5][6][7][8] .Similar trends for greater fall of SBP in RA patients was noted by Louthreno et al 5 .and less rise of DBP was reported by Sandhu and Allen 6 whereas similar results in both parameters were also reported 2 .…”
Section: Discussionsupporting
confidence: 58%
“…The autonomic nervous system plays very important role in regulating cardiovascular homeostasis and RA may cause autonomic imbalance which is not well studied as well as presented conflicting results 5 . Higher sympathetic activity in RA was reported by some studies 5 whereas others found sympathetic dysfunction in RA 6 . Recently, orthostatic hypotension was found in 8% of RA patients 2 .…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…These suggestions like immune complex deposition, amyloid deposition, autoantibody production against nerve growth factor, cervical ganglia and vagus nerve may act as causative factors for this autonomic nerve function impairment in patients of the present series. 10,17,23 But all of them were not possible to study due to some limitation.…”
Section: Discussionmentioning
confidence: 99%